PENGARUH KUALITAS PELAYANAN, KEPUASAN DAN NILAI NASABAH TERHADAP LOYALITAS NASABAH SIMPAN PINJAM PADA KUD “TANI JAYA” KECAMATAN PUNCU - Nurfadila, Kharisma (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study generally aims to determine the effect of service quality, satisfaction and value of savings and loan customers on customer loyalty at the Village Unit Cooperative "TANI JAYA" Puncu sub-district. The research approach used is quantitative. The population of this study is a portion of savings and loan customers who are active as cooperative customers as many as 40 people. The sample of this study has a population of less than 100 people, so the total sample is taken as a whole. Data collection used a questionnaire which was analyzed using multiple linear analysis. The results of this study the researchers revealed that service quality, satisfaction and customer value partially were only satisfaction variables which did not have a significant effect, but simultaneously all variables had a significant effect on customer loyalty.